Accounting for Savings, Buillding, and Loan Associations (Book). - Hanson, Arthur W. (The Accounting Review, 1932)
Reviews the book "Accounting for Savings, Building, and Loan Associations," vol. 1, "Savings, Building, and Loan Bookeeping," by John R.B. Byers.